Paediatric Burkitt lymphoma patient-derived xenografts capture disease characteristics over time and are a model for therapy - Forde, Sorcha; Matthews, Jamie D; Jahangiri, Leila; Lee, Liam C; Prokoph, Nina; Malcolm, Tim I M; Giger, Olivier T; Bell, Natalie; Blair, Helen; O'Marcaigh, Aengus; Smith, Owen; Kenner, Lukas; et al. (British journal of haematology, 2021)
Burkitt lymphoma (BL) accounts for almost two-thirds of all B-cell non-Hodgkin lymphoma (B-NHL) in children and adolescents and is characterised by a MYC translocation and rapid cell turnover. Intensive chemotherapeutic regimens have been developed in recent decades, including the lymphomes malins B (LMB) protocol, which have resulted in a survival rate in excess of 90%. Recent clinical trials have focused on immunochemotherapy, with the addition of rituximab to chemotherapeutic backbones, showing encouraging results. Despite these advances, relapse and refractory disease occurs in up to 10% of patients and salvage options for these carry a dismal prognosis. Efforts to better understand the molecular and functional characteristics driving relapse and refractory disease may help improve this prognosis. This study has established a paediatric BL patient-derived xenograft (PDX) resource which captures and maintains tumour heterogeneity, may be used to better characterise tumours and identify cell populations responsible for therapy resistance.
Keywords: relapse; regulace genové exprese u nádorů; Humans; B-cell lymphoma; Tumor Cells, Cultured; dítě; Burkittův lymfom; Burkitt lymphoma; Child; Female; heterografty; lidé; patient derived xenograft; zvířata; myši; Mice; nádorové buňky kultivované; murine cancer models; ženské pohlaví; Male; Neoplasm Transplantation; transplantace nádorů; Animals; Heterografts; mužské pohlaví; Gene Expression Regulation, Neoplastic; Disease Models, Animal; Burkitt Lymphoma; modely nemocí na zvířatech